Logistical gazes: introduction to a special issue of Work Organisation, Labour and Globalisation. (1st April 2019) - Benvegnù, Carlotta; Cuppini, Niccolò; Frapporti, Mattia; Milesi, Floriano; Pirone, Maurilio
Abstract : This article introduces this special issue of Work Organisation, Labour and Globalisation on logistics. First of all, it furnishes a brief genealogy of logistics in the modern era. Then, it frames some of the main issues in current critical debates on logistics. Finally, it presents the contents of the special issue in detail, connecting them with more general attempts to develop a 'logistical gaze' as a methodological perspective on the different and multiple transformations of contemporary capitalism.